(3QaY GdZTGA aj hbJi GdYUQ hGdYTGAs - (3Rjf GdOjf Hf EHQGgje Hf eMeO Hf fLje GdeUQj GdMfaj , GHf fLje,J (B970 (3g` s ((3bGSe Hf jhSa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi jfUQ GdMb hdh HYO Mjf hHYO agPg QSGdI ai hbJi GdYUQ hGdYTG Ydi ePgH GdGeGe GdGYXe CHj MfjaI GdfYeGf s
(3BNQgG (B:s
(3aKHJ Cf bhd GdGeGe gh GdCUM ceG GNJGQg GdfSai bGd GdeDda QMeg Gddg JYGdi hQVi Yfg hcGf Pdc ai ChGNQ TYHGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B192 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B378s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B910s
Keywords: (3Gdabg GdMfajs